Examining the Effect of Road Traffic Congestion on Stress at Work: Do Perceived Organizational and Supervisor’s Support Really Help? - Agung Minto Wahyu; Alice Salendu (Universitas Muhammadiyah Metro, 2026)
Traffic congestion can lead to various negative consequences for individuals. One of the most disruptive consequences for workers is stress at work. This study aims to examine the relationship between road traffic congestion and stress at work, with perceived organizational support and perceived supervisor support as moderators. A quantitative method with an online survey was conducted on 213 workers in Indonesia who experience traffic congestion while commuting to work or from work. Data analysis was performed using Hayes’s PROCESS macro in IBM SPSS Statistics version 26 with model 2 for moderated regression analysis. The result indicates that road traffic congestion significantly affects stress at work (ÃŸ = 0.63, p <0.05, CI = [0.48, 0.78]). However, perceived organizational support was not significant in the role of moderator between road traffic congestion and stress at work (-0.12, 95% CI = [-0.29, 0.05]). In addition, perceived supervisor support did not play a role as a moderator between road traffic congestion and stress at work (0.09, 95% CI = [-0.13, 0.31]). These findings demonstrate that the negative consequences of road traffic congestion are very substantial that their impact on stress at work does not diminish even though workers have perceived organizational and supervisor support.